Analisis Faktor Predisposisi Dan Presipitasi Gangguan Jiwa Di Ruang Instalasi Gawat Darurat Rumah Sakit Jiwa Daerah Surakarta - Indah Saputri, Asykari; Arum Pratiwi, S.Kep, M.Kep (2016)
ABSTRACT Mental disorder is case/disease that give directly, but patients are likely to have trouble socializing with the environment and pose a burden for the family. Currently patients with mental disorders has increased quite rapidly. The high growth of human and live load problems cause a person vulnerable to mental disorders. This study aims to investigate the predisposing factors and precipitation of mental disorders in the Mental Hospital of Surakarta. Janis Research is a descriptive analytic with cross sectional approach. The study population was patients who enter the emergency room in 2015 the average - average amounted to 227 patients. A sample of 56 patients were taken by accidental sampling technique. Collecting data using the questionnaires and then analyzed using analysis of central tendency. Conclusion The study showed a predisposing factor in patients with mental disorders are caused by loss, failure and grief. While precipitation factors in patients with mental disorders are psychological disorders, social disorders, emotional disorders and biological disorders. Keywords: predisposing factors, precipitation factors, mental disorders